BEST INTEREST OF THE CHILD IN ISLAMIC FAMILY LAW: INTEGRATING MAQĀṢID AL-SHARĪ‘AH AND DOUBLE MOVEMENT THEORY IN ḤAḌĀNAH CASES - Kadarisman , Achmad; Fedro, Alfarid; Arifin, Zainal (Institut Agama Islam Negeri Bone, 2025)
This study examines the development of ḥaḍānah (child custody) in Indonesian Islamic family law, tracing its shift from classical fiqh principles toward contemporary child-centered standards. Classical jurisprudence conceptualizes ḥaḍānah as the obligation to nurture and protect those unable to care for themselves, traditionally privileging maternal custody. In Indonesia, however, statutory and judicial practice increasingly reflect welfare-oriented interpretations. Using a qualitative normative–empirical approach, this research analyzes fiqh texts, national legislation, the Compilation of Islamic Law (KHI), international child-rights instruments, and selected custody decisions, complemented by interviews with judges and affected families. Analytical guidance is drawn from maqāṣid al-sharīʿah and Fazlur Rahman’s double-movement theory to contextualize classical norms within modern Indonesian realities. The findings reveal a hybrid legal framework: while fiqh-based custodial hierarchies remain codified, courts frequently rely on the best interest of the child when evaluating parental claims, caregiving continuity, and emotional well-being. Children’s testimonies are increasingly considered, though inconsistently applied across cases. The study demonstrates how Islamic legal reasoning can be harmonized with universal child-rights principles. It concludes by emphasizing the need for strengthened mediation, child-sensitive adjudication, and institutional mechanisms that ensure meaningful child participation in custody determinations.